Unveiling The Discourse of Fraud in The United States Presidential Election 2020 with Normal Fairclough Critical Discourse Analysis - Nasirudin, Didin (Syntax Literate, 2024)
The political rise of Donald Trump in the United States was unprecedented, characterized by his deviation from traditional political norms and his use of divisive rhetoric against minorities, Muslims, China, and immigrants. Trump's strategy of galvanizing conservative white Evangelicals led to his unexpected victory in the 2016 presidential election. During his 2020 reelection campaign, Trump employed similar tactics; however, his handling of the COVID-19 pandemic and the resulting economic downturn eroded his support compared to his Democratic rival, Joe Biden. Anticipating electoral defeat, Trump preemptively alleged widespread electoral fraud, specifically targeting mail-in voting policies. After losing the election, with an electoral count of 232 to Biden's 306, Trump continued to claim the election was "rigged," asserting voter fraud via Twitter. Despite numerous court dismissals of these claims, a significant portion of the Republican base accepted Trump's narrative, which culminated in the January 6 Capitol riot intended to obstruct the certification of Biden's victory. This study aims to analyze the impact of Trump's rhetoric on his supporters' beliefs and actions. The research employs qualitative methods, including content analysis of Trump's tweets and media coverage, alongside quantitative analysis of public opinion polls, to examine the correlation between Trump's fraud claims and the Capitol riot. The findings indicate a strong influence of Trump's rhetoric on his supporters, underscoring the profound effect of political discourse on public perception and behavior. The conclusion highlights the critical need for responsible political communication to uphold democratic integrity.